IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AT PT. XYZ - Yanto Tjia (Dinasti Publisher, 2020)
Good Corporate Governance can be understood as a concept that encompasses various aspects of a company (corporate structure, division of duties and responsibilities, division of authority, to all aspects / elements that form the company) including the mechanisms that must be carried out by each aspects of the company. A good company is a company that is able to carry out business ethics in carrying out its daily operations, and this is generally done through the implementation of GCG (Good Corpoate Governance) / Corporate Governance. The purpose of this study for the author is to know and understand how GOOD CORPORATE GOVERNANCE IMPLEMENTATION at PT. XYZ The research method that I use in this research is descriptive qualitative analysis method and literature study, with the aim of getting information carefully to find out the concept and IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE at PT. XYZ